Some aspects of the reproductive endocrinology of the catfish, Clarias Gariepinus (Burchell, 1822) - Rennie, Susan Elizabeth (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1981)
A description is given of the location, anatomy and morphology of the endocrine glands likely to be involved in controlling the reproductive cycle of C. gariepinus. Methods of identifying the secretory tissues in the light and electron microscopes are outlined. A review of the published results on homologous tissues from other teleosts is included and directions for further research on the endocrinology of C. gariepinus are discussed.
Keywords: Catfishes; Clarias gariepinus